PENGARUH COGNITIVE BEHAVIORAL THERAPY (CBT) TERHADAP POST TRAUMATIC STRESS DISORDER (PTSD) PADA PASIEN POST KECELAKAAN LALU LINTAS DI RSUP SANGLAH DENPASAR - Prabandari, Diah (Coping: Community of Publishing in Nursing, 2015)
Post Traumatic Stress Disorder (PTSD) is a disease caused by maladaptive response of the traumatic process that is endured by the patient. The traumatic can be caused by various reasons, one of them is traffic accidents. In a way PTSD can be treated well if it is detected as early as possible. The management of PTSD includes pharmacotherapy and psychotherapy. One of the forms regard the psychotherapy that is effective in the treatment of PTSD, namely the method of Cognitive Behavioral Therapy (CBT). This study was a pre-experimental design study (one group pretest-posttest design) and aimed to reduce grievances of PTSD as seen from the average of PSS scores before and after treatment. In this study, the cases of PTSD were selected by PTSD Symptom Scale (PSS) then there were 15 samples selected as research respondent through purposive sampling technique. The data was collected by interview method then used to complete the PSS questionnaire. The result of statistical tests of Paired T-Test showed there were differences average PSS scores with a significance level of p =0,000. It means CBT have a significant effect in reducing the signs and symptoms of PTSD in patients with post-traffic accident. Based on the findings above, it is suggested to the nurse/the other health professionals use CBT as one of the possible interventions to reduce grievances and symptoms of PTSD.
Keywords: PTSD, maladaptive response, CBT